IoT-Based Smart Feed Management System Using Load Cell Sensors for Catfish Farming - Ahmad Ramdoni; Fikri Arif Wicaksana (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Feed management is one of the key factors influencing the growth performance and production efficiency of catfish farming. However, in many small-scale and medium-scale aquaculture operations, feeding activities are still carried out manually, which often results in inconsistent feed portions, irregular feeding schedules, and limited control over feed stock availability. These conditions can affect fish growth and increase production costs. This study presents the development of an Internet of Things (IoT)-based smart feed management system designed to support accurate feed distribution and feed stock monitoring. The proposed system uses a NodeMCU ESP32 microcontroller, a load cell sensor to measure feed weight for accurate feed portion control, and an ultrasonic sensor for monitoring feed stock levels. Feed is released according to a predefined feeding requirement, while sensor data are transmitted through an IoT network for real-time monitoring. Telegram integration is implemented to provide notifications regarding feed stock status, daily feed usage, and estimated feed requirements. System testing demonstrated that the proposed solution was capable of automatically dispensing feed according to the calculated feed portions, monitoring feed stock conditions remotely, and providing notifications to users via Telegram. The developed system can assist fish farmers in improving feeding accuracy, reducing feed waste, enhancing operational efficiency, and supporting sustainable aquaculture management.